Carbon and nitrogen stocks and organic matter light fraction in a Typic Quartzipsamment under agricultural use - Frazão, Leidivan Almeida; Santana, Ingrid Kely da Silva; Campos, David Vilas Boas de; Feigl, Brigitte Josefine; Cerri, Carlos Clemente (Pesquisa Agropecuaria Brasileira, 2011)
The objective of this work was to evaluate C and N stocks in the soil and their contents in the free light fraction (FLL) of the soil organic matter (MOS), in a Typic Quartzipsamment under different land-use in Cerrado. Five areas were selected for evaluation: native cerrado; two areas with soybean under conventional tillage; one area formerly under pasture and afterwards cultivated with soybean under no-tillage; and one area under pasture with low productivity. Soil samples were collected from 0-5, 5-10, 10-20 and 20-30-cm depth layers to determine total C and N stocks of the soil. Contents of C and N in the FLL were determined at 0-5 and 5-10-cm depth. An increase was observed in the total C stocks in soybean areas implemented until five years, in comparison to the native cerrado area. There was a reduction in the amount of FLL and C content at 0-5 cm depth, in areas with soybean and pasture. Considering the low C and N natural input onto the Typic Quartzipsamment, the adoption of agricultural systems that can promote an adequate supply of residues is necessary for maintaining or increasing the soil organic matter.